Comportamento da atividade de renina plasmática mediante exercício físico na hipertensão arterial e sobrepeso - Martinelli, Bruno; Arca, Eduardo Aguilar; Franco, Roberto Jorge da Silva [UNESP]; Martin, Luis Cuadrado [UNESP] (My University, 2011)
Background and objectives: There are evidences that the plasmatic renin system’s activity is a mediator of the connection between obesity and hypertension. Obese and sedentary people have most intense activation of this system, what could, at least in parts, explain the high cardiovascular damage among these individuals. The aerobic exercise influences this enzymatic activity, which makes it an important element for therapeutic intervention in both clinical conditions mentioned. This study’s aim was to discuss the interactions among renin system, hypertension, obesity and physical exercise. Contents? The clinical evidences indicate a positive effect of the physical exercise over the renin-angiotensin-aldosterone axis. The effect of acute physical exercise promotes increase of the plasmatic renin activity levels; and, at long-term, it could causes relative reduction in hypertensive patients. Conclusion:There are controversies concerning the several modulating interactions of these elements and the plasmatic renin activity’s response, which leads to the need of further investigation. Moreover, the available studies were not able to clearly evidence a direct effect of this enzymatic system activation in the trinomial: hypertension, overweight and sedentary life

Justificativa e objetivos: Existem evidências de que a atividade do sistema renina plasmático participa da ligação entre obesidade e hipertensão arterial. Obesos e sedentários têm tendência à ativação mais intensa desse sistema, o que poderia explicar, pelo menos em parte, o maior comprometimento cardiovascular desses indivíduos. O exercício aeróbio influencia a atividade enzimática desse sistema, tornando-o importante elemento de intervenção terapêutica para as duas condições clínicas citadas. O objetivo deste estudo foi discutir as interações entre sistema renina, hipertensão arterial, obesidade e exercício físico. Conteúdo: As evidências apontam para um efeito positivo do exercício físico sobre o eixo renina-angiotensina-aldosterona. O efeito agudo do exercício induz elevação dos níveis da atividade de renina plasmática, e em longo prazo, pode causar diminui- ção relativa em portadores de hipertensão. Conclusão: Há controvérsias sobre a modulação da resposta da atividade da renina plasmática na obesidade e sedentarismo, o que mostra a necessidade de mais investigações nessa área. Além do mais, os estudos disponíveis não evidenciaram claramente um efeito direto da ativação dessa enzima no trinômio: hipertensão, obesidade e sedentarismo.
Plasmatic renin activity and physical exercise in hypertension and obesity
Keywords: Exercise; Hypertension; Obesity; Renin; Exercício; Hipertensão; Obesidade; Renina